Boosting Drug Treatment Attendance Through Police-Sent Text Message Nudges: A Randomized Controlled Trial with Drug-Positive Arrestees - Dwyer, Paul (American journal of criminal justice, 2025)
Attrition from drug treatment programs is a ubiquitous concern, but less is known about effective strategies to assist people with an addiction in arriving at the initial intake meeting. This study investigates whether text message reminders sent to drug-positive arrestees to participate in mandated drug treatment appointments increase attendance rates. We conducted a randomized controlled trial in London, and participants were randomly assigned to either a treatment group (n = 403) receiving a text message reminder or a control group (n = 410) receiving no text message. Participants were arrestees with a verified mobile phone number who tested positive for Class A drugs at intake across 25 custody suites and were scheduled for a drug treatment assessment at one of London’s 28 treatment facilities. The primary outcome was the attendance rate at drug treatment centers, which was analyzed using an ordinary least squares regression model. Results suggest that nudges have the potential to increase attendance at drug treatment centers among drug-positive arrestees. Although we have no additional outcome variables, the intervention shows promise as a cost-effective strategy for enhancing compliance with mandated rehabilitations. Future research should explore this intervention’s broader implications and effectiveness across diverse and more extensive samples.